That infernal little Cuban republic : the United States and the Cuban Revolution - Schoultz, Lars (University of North Carolina Press, 2009)
Presents a comprehensive chronicle of US policy towards the Cuban revolution. This book tells the story of the attempts and failures of ten US administrations to end the Cuban Revolution.